PK‐guided personalized prophylaxis with Nuwiq® (human‐cl rhFVIII) in adults with severe haemophilia A. Issue 5 (27th April 2017) - Lissitchkov, T.; Rusen, L.; Georgiev, P.; Windyga, J.; Klamroth, R.; Gercheva, L.; Nemes, L.; Tiede, A.; Bichler, J.; Knaub, S.; Belyanskaya, L.; Walter, O.; et al.
Abstract : Introduction: Nuwiq ® (human‐cl rhFVIII) is a 4 th generation recombinant human FVIII, without chemical modification or protein fusion, produced in a human cell‐line. Aims/Methods: This study (NuPreviq) was a prospective, open‐label, multicentre, phase IIIb study of the efficacy and safety of personalized prophylaxis with Nuwiq ® in 66 previously treated adults with severe haemophilia A. NuPreviq had three phases: (i) a 72‐h pharmacokinetic (PK) phase; (ii) a 1–3 month standard prophylaxis phase; and (iii) a 6‐month personalized prophylaxis phase. The personalized prophylaxis regimen was based on individual PK modelling for each patient according to whether their PK profile most closely fitted a two‐ or one‐compartment model (NuPreviq approach). In cases of uncertainty, a noncompartment model was applied. Results: The median dosing interval during personalized prophylaxis was 3.5 days, with 57% of patients on ≤2 weekly dosing. Mean annualized bleeding rates during personalized prophylaxis were 1.45 (median [interquartile range, IQR]: 0 [0, 1.9]) for all bleeds, 0.79 (median [IQR]: 0 [0, 0]) for spontaneous bleeds, and 0.91 (median [IQR]: 0 [0, 0]) for joint bleeds. During personalized prophylaxis, 83.1% of patients were spontaneous bleed‐free. Compared with standard prophylaxis, median weekly prophylaxis dose was reduced by 7.2% from 100.0 to 92.8 IU kg −1 during the last 2 months of personalized prophylaxis. There were no FVIII inhibitors or treatment‐related serious or severe adverse events. Conclusion: PK‐guided personalized prophylaxis with Nuwiq ® provided bleeding protection and enabled the dosing interval to be extended to twice weekly or less in many patients and an overall dose reduction.